It's a long way from Llano : the journey of a wildlife biologist - Teer, James G. (Texas A & M University Press, 2008)
Wildlife management around the world has changed drastically in the last fifty years, and veteran biologist James G. Teer was a trailblazer for much of that time. In this memoir, he looks back on his life and on the transformation of his profession. A pioneer in managing land for deer, Teer became truly global in his conservation efforts. From studying waterfowl in Manitoba and monitoring deer herds in the Texas Hill Country, Teer was propelled into the world of big ranches and African safaris, working for and traveling with Texas landowners while helping to build the reputation of the wildlife ecology program at Texas A&M University. As he reminisces, Teer gives homage to the men who mentored and taught him and to those whose friendships lasted a lifetime. He salutes his colleagues and his students, and he confirms his lifelong commitment to the care and stewardship of animals everywhere.